Organic hallucinosis at pituitary macroadenoma (case report). - I. D. Spirina; S. F. Leonov; T. Yo. Shusterman; Ya. S. Varshavs'kij; V. A. Mihal'ova (Medičnì Perspektivi)
The article describes the clinical case of organic hallucinosis, the beginning of which is definitelyassociated with pituitary macroadenoma. Complex hallucinations (visual, auditory, olfactory, tactile) with zoological theme are brightly presented in the clinical picture of the disorder. Due to refusal of the patient from neurosurgical intervention for removingof pituitary adenoma the extinction of hallucinatory symptoms can not be reliably measured, and the presence of atherosclerotic changes in cerebral vessels, concomitant arterial hypertension increase the likelihood of permanent or recurrent nature of hallucinosis and make prognosis for recovery as unfavorable.